Microstructure gradients across the white etching and transition layers of a heavy haul pearlitic steel - Ribamar, G. G.; Pereira, J. I.; Escobar, J. D.; Avila, J. A. [UNESP]; Lopes, J. G.; Maawad, E.; Schell, N.; Oliveira, J. P.; Goldenstein, H.; Souza, R. M. (Elsevier, 2024)
This study delves into the frequent surface cracking observed in severely damaged pearlitic carbon steel rails, a phenomenon often attributed to the challenging characteristics of the white etching layer (WEL) formed during railway operations. To explore this issue, a severely damaged rail cross-section featuring a substantial WEL layer measuring 600 μm in depth was analyzed. The WEL's size was initially determined through optical microscopy and characterized via nano-hardness testing, which revealed an impressive hardness of up to 12 GPa. High-energy synchrotron X-ray diffraction (HESXRD) analysis was employed to uncover the crystalline structure diversity gradient that resulted from railway use. The results unveiled that cumulative high-temperature surface damage leads to the formation of both the WEL and a transitional layer. Within this transitional layer, a gradual reduction in retained austenite is observed, coupled with an increase in the presence of cementite and ferrite as one approaches the base metal. Remarkably, very shallow depths from the surface display tempered martensite characteristics, characterized by high nanohardness, lower dislocation density, and an initially smaller, then increasing austenite fraction. The use of site-resolved synchrotron radiation diffraction at different depths from the surface to the interior of the damaged rail cross-section allowed a unique insight into the phase transformations, microstrain developments, and compositional evolution.
Keywords: Heavy haul railway; Pearlitic steel; Synchrotron X-ray diffraction; Transitional layer; White etching layer